Pengaruh Intellectual Capital Terhadap Kinerja Perusahaan dengan Corporate Governance Sebagai Variabel Intervening Pada Perusahaan Perbankan - Dariati, Anis Mahmudah; Heriyani, Heriyani; Mustika, Dama (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2023)
This research covers 36 banking companies listed on the Indonesia Stock Exchange during the 2021-2022 period and focuses on the influence of intellectual capital on corporate performance. The criteria established the sampling method, which resulted show several important findings, which resulted from data analysis carried out using the SEM-PLS method. First, research shows that intellectual capital has a positive influence on corporate governance. Second, there was no significant influence of intellectual capital (VAIC) on corporate governance. Third, there was a positive influence of corporate governance on corporate performance. And fourth, there was no significant influence of intellectual capital on corporate performance through corporate governance.